TINGKAT KEPATUHAN DAN PENGETAHUAN PEGAWAI FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM SUMATERA UTARA TERHADAP PROTOKOL KESEHATAN COVID-19: COMPLIANCE AND KNOWLEDGE LEVEL ANALYTIC OF THE MEDICAL FACULTY UISU EMPLOYEES AGAINST THE HEALTH PROTOCOL OF COVID-19 - Icha Yuniati; Indra Janis (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2025)
Covid-19 is a global pandemic spread across 215 countries including Indonesia. Employees are workers who are very vulnerable to being infected with Covid-19. This is associated with the high activity of employees in closed spaces such as offices. The best way to prevent transmission of Covid-19 is to avoid direct contact by implementing the 5M. This study aims to determine the relationship between the level of adherence and knowledge of staff at the Faculty of Medicine, Islamic University of North Sumatra towards the Covid-19 health protocol. This research is analytic observational with a cross-sectional study design. This research was conducted at the Faculty of Medicine, Islamic University of North Sumatra in December 2022 - January 2023. The sample in this study were all UISU Faculty of Medicine employees with a total sample of 50 people. Data taken through a questionnaire and analyzed using the Gamma Test. Of the 50 samples, 32 respondents (64%) had high compliance, 19 respondents (38%) had sufficient knowledge. There is a strong and significant relationship between compliance and knowledge of the Covid-19 health protocol with p-value = 0,000 or p <0,05. AbstrakVirus jenis baru Severe Acute Respiratory Syndrome-Coronavirus -2 (SARS-CoV-2) dengan nama umumnya dikenal sebagai Corona Virus Disease 2019 (Covid-19). Covid-19 adalah sebuah pandemi global. Kasus ini tersebar di 215 negara termasuk Indonesia. Pegawai merupakan pekerja yang sangat rentan terinfeksi Covid-19. Hal ini dikaitkan dengan tingginya aktivitas pegawai dalam ruangan tertutup seperti perkantoran. Cara terbaik untuk mencegah penularan COVID-19 adalah menghindari kontak langsung dengan menerapkan 5M. Mengetahui hubungan tingkat kepatuhan dan pengetahuan pegawai Fakultas Kedokteran Universitas Islam Sumatera Utara terhadap protokol kesehatan covid-19. Penelitian bersifat analitik observasional dengan desain studi Cross sectional. Penelitian ini dilaksanakan di Fakultas Kedokteran Universitas Islam Sumatera Utara pada Bulan Desember 2022 – Januari 2023. Sampel dalam penelitian ini adalah seluruh pegawai FK UISU dengan jumlah sampel 50 orang. Data yang diambil melalui kuesioner dan di analisis menggunakan Uji Gamma. Dari 50 sampel, 32 responden (64%) pegawai berkepatuhan tinggi, 19 responden (38%) berpengetahuan cukup. Terdapat hubungan yang kuat dan signifikan antara kepatuhan dan pengetahuan terhadap protokol kesehatan covid-19 dengan nilai p-value =0,000 atau p <0,05. A new type of virus called Severe Acute Respiratory Syndrome-Coronavirus -2 (SARS-CoV-2) with the common name known as Corona Virus Disease 2019 (Covid-19). Covid-19 is a global pandemic. This case is spread across 215 countries including Indonesia. Employees are workers who are very vulnerable to being infected with Covid-19. This is associated with the high activity of employees in closed spaces such as offices. The best way to prevent transmission of COVID-19 is to avoid direct contact by consistently implementing 5M. To determine the relationship between the level of adherence and knowledge of employees of the Faculty of Medicine, Islamic University of North Sumatra regarding the Covid-19 health protocol. This research is analytic observational with a cross-sectional study design. This research was conducted at the Faculty of Medicine, Islamic University of North Sumatra in December 2022-January 2023. The sample in this study were all UISU Faculty of Medicine employees with a total sample of 50 people. Data taken through questionnaires and analysis using the Gamma Test. Of the 50 samples, 32 respondents (64%) had high compliance, 18 respondents (38%) had sufficient knowledge. Based on the results of this study, it can be concluded that there is a strong and significant relationship between compliance and knowledge of the Covid-19 health protocol with a p-value = 0.000 or p <0.05.